REVIEW ARTIKEL : PRODUKSI BIODIESEL DARI MINYAK GORENG BEKAS DENGAN METODE TRANSESTERIFIKASI MENGGUNAKAN KATALIS - Budiman, Aditya Arif; samik, samik (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2023)
Waste frying oils are renewable energy raw materials that can be used to produce biodiesel at more economical production costs because they are waste and are cheap or even free. The use of WFO as a biodiesel raw material is an environmentally friendly measure as it can reduce environmental pollution, especially in soil and rivers. Therefore, the purpose of this article is to explain the processing of WFO into biodiesel raw materials with a variety of catalysts, including acid, base, and enzyme catalysts that are both homogeneous and heterogeneous. The method used in writing this article is to review various articles on the production of biodiesel with the transesterification method using catalysts that are acidic (homogenic and heterogenic), bases (homogenic and heterogenic), and enzyme catalysts. Results from various studies suggest that WFO can be converted into biodiesel using a variety of catalysts. Under optimal conditions, homogeneous acid catalysts such as H2SO4 produce yield biodiesel at 95.37%. Heterogeneous acid catalysts such as Fe2O3-MnO-SO42- / ZrO2 produce a yield of 96,5%. Homogeneous base catalysts such as NaOH produce a biodiesel yield of 98%. Heterogeneous base catalysts such as CaO-MgO produce biodiesel yields of 98,95%. Enzyme catalysts such as Lipase enzyme from Candida rugosa and Rhizomucor miehei produce biodiesel yields of 96,5%. From these results, the heterogeneous base catalyst CaO-MgO is the catalyst with the highest yield in producing biodiesel among various other catalysts